Between Engagement and Real Impacts: A Literature Review of Library Social Media Promotion in Indonesian Libraries Using the AIDA Model - Zaskia Julia Putri Rahmadani; Faisal Fahmi; Rahmandani, Charissa (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2026)
Purpose Research. This study critically examine the effectiveness of social media promotion strategies implemented by libraries in using AIDA model (Attention, Interest, Desire, Action) as a conceptual framework. Research Methods. This study employs a literature review method using secondary data from journal articles, theses, and institutional reports published between 2019 and 2025. Analysis Data. The data were systematically analyzed using six thematic dimensions: platform selection, content strategy, engagement quality, success metrics, structural barriers, and strategic alignment, with a qualitative-descriptive and critical approach. Results. Instagram dominates as the primary promotional platform. However, most library only achive the Attantion stage, with minimal progression to Interest, Desire, and Action. Engagement metrics remain surface-level, disconnected from measurable behavioral outcomes such as library visits or service utilization. Social media has not been strategically as a promotion tool in Indonesia libraries. This study contributes a critical AIDA-based evaluative framework that bridges the gap between engagement metrics and real impact, offering practical implications for integrated content planning and impact-based evaluation in library management. Keywords: Social Media Promotion; Libraries; AIDA Model; Indonesian Libraries